Degradation Of Shrimp Waste Using Chitinase Produced By Trichoderma Virens UKM1 Through Media Selection - Teoh, Lay Sin (2008)
The current increase in the amount of seafood wastes produced by the shrimp industry has led to the finding of new methods for shrimp waste disposal or its recycle. Chitinaseproducing fungi is investigated to be used as a biocontrol agents in particular their potential for waste degradation of shrimps and crab shells from fishing industry. Locally isolated Trichoderma virens UKM1 expressing chitinases enzyme was used in this study. Three types of media were selected namely Medium 4, Medium 5 and Trichoderma minimal medium (TMM) for the degradation study. The substrate used was colloidal chitin as control substrate, ground and unground sun-dried shrimp shell wastes. Scanning Electron Microscopy (SEM) studies showed penetration of fungus mycelium into the colloidal chitin as compared to ground and unground sun-dried shrimp shells. Trichoderma virens UKM1 in TMM produced the less biomass and highest chitinase enzyme and in Medium 4 the protein concentration is the highest if compared with other media used. The results obtained suggested that colloidal chitin was the best carbon source for modelling the degradation of chitin materials. Stereo microscope studies showed that the mechanism of chitinous materials degradation by the chitinase enzyme is via sequential degradation. Shrimp wastes were further analysed for end products in the crude media using High Performance Liquid Chromatography (HPLC). Results showed that the Trichoderma virens UKM1 secretes a significant amount of exochitinase compared to endochitinase by the identification of monomeric N- acetylglucosamine (NAG) from the chitinous substrate. Trichoderma virens UKM1 produced more NAG using TMM with colloidal chitin as the substrate.